TRNA wobble modifications and protein homeostasis. Issue 1 (2nd January 2016) - Ranjan, Namit; Rodnina, Marina V.
Abstract: tRNA is a central component of the protein synthesis machinery in the cell. In living cells, tRNAs undergo numerous post-transcriptional modifications. In particular, modifications at the anticodon loop play an important role in ensuring efficient protein synthesis, maintaining protein homeostasis, and helping cell adaptation and survival. Hypo-modification of the wobble position of the tRNA anticodon loop is of particular relevance for translation regulation and is implicated in various human diseases. In this review we summarize recent evidence of how methyl and thiol modifications in eukaryotic tRNA at position 34 affect cellular fitness and modulate regulatory circuits at normal conditions and under stress.